Investigation of the Effect of Exhaust Middle Pipe Length to the Engine Performance - Tuan Nur Aiman Bin Tuan Kamaruddin, Tuan Nur Aiman (Universiti Teknologi Petronas, 2008)
The objective of this project is to investigate the effect of exhaust middle pipe length with respect to the engine performance. Backpressure always exists in any exhaust piping system. Backpressure is related to pumping loss or pressure required to push out the gas from the combustion chamber. Diameter and length of the exhaust pipe can affect the flow of the gasses. Free flowing gasses will reduce the pumping loss. This project interest is length of the pipe. The diameter of the pipe will be constant while the length will be varied.